St. John’s wort attenuates colorectal carcinogenesis in mice through suppression of inflammatory signaling - Manna, Soumen K. (Cancer Prev Res (Phila), 2015)
In spite of widespread use as well as epidemiological indications, there have been no investigations into the effect of St. John’s wort (SJW) extract on colorectal carcinogenesis in vivo. This study reports a systematic evaluation of the impact of dietary supplementation of SJW extract on azoxymethane (AOM)-induced colorectal carcinogenesis in mice. Mice were fed with either AIN-93G (control) diet or SJW extract-supplemented diet (SJW diet) prior to AOM treatment. SJW diet was found to significantly improve the overall survival of AOM-treated mice. Pre-treatment with the SJW diet significantly reduced body weight loss as well as decrease of serum albumin and cholesterol levels associated with AOM-induced colorectal tumorigenesis. SJW diet-fed mice showed a significant decrease in tumor multiplicity along with a decrease in incidence of large tumors and a trend towards decreased total tumor volume in a dose-dependent manner. A short-term study, which examined the effect of SJW prior to rectal bleeding, also showed decrease in colorectal polyps in SJW diet-fed mice. Nuclear factor kappa B (NF-κB) and extracellular signal-regulated kinase (ERK 1/2) pathways were attenuated by SJW administration. SJW extract resulted in early and continuous attenuation of these pathways in the colon epithelium of SJW diet-fed mice under both short term and long term treatment regimens. In conclusion, this study demonstrated the chemopreventive potential of SJW extract against colorectal cancer through attenuation of pro-inflammatory processes.